The Effect of Ratio of Pineapple Juice with Katuk Leaf Juice and Carrageenan Concentration on the Quality of Jelly Candy - Misye A. Lumbangaol; Rona J. Nainggolan; Era Yusraini (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of this research was to find the effect of ratio of pineapple juice and katuk leaf juice and carrageenan concentration on the quality of jelly candy. This research was using completely randomized design with two factors, i.e ratio of pineapple juice and katuk leaf juice (S): (90%:10%, 80%:20%, 70%:30%, 60%:40%) and carrageenan concentration (K) (2%, 3%, 4%). The results showed that the ratio of pineapple juice and katuk leaf juice had highly significant effect on moisture content, ash content, protein content, vitamin C content, total acid content, total soluble solid content, total lactic acid bacteria content, organoleptic scores value of color, flavour and taste. Carrageenan concentratiton had highly significant on ash content, total acid content, total soluble solid content, and had significant effect on moisture content and vitamin C content. The interaction of the two factors had highly significant effect on total acid content and had significant effect on ash content. The ratio of pineapple juice and katuk leaf juice of 80%:20% (S2) and carrageenan of 2% (K1) produced the best jelly candy Keywords : Jelly Candy, Pineapple, Katuk Leaf, Carrageenan.